2012
DOI: 10.1016/j.watres.2012.01.040
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal variation in indicator microbe sampling is influential in beach management decisions

Abstract: Fecal indicator microbes such as enterococci are often used to assess potential health risks caused by pathogens at recreational beaches. Microbe levels often vary based on collection time and sampling location. The primary goal of this study was to assess how spatial and temporal variations in sample collection which are driven by environmental parameters impact enterococci measurements and beach management decisions. A secondary goal was to assess whether enterococci levels can be predictive of the presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
48
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 30 publications
4
48
1
1
Order By: Relevance
“…We found that community changes correlated with nutrient concentrations in berm sand. Nutrients are relatively more conserved than E. coli and enterococci, which can die off in short periods of time and be highly transient (50,(54)(55)(56)(57). These findings support that nutrient concentrations and microbial communities are relatively stable over time and reflect longer-term conditions at a beach better than densities of fecal indicators.…”
Section: Discussionmentioning
confidence: 52%
“…We found that community changes correlated with nutrient concentrations in berm sand. Nutrients are relatively more conserved than E. coli and enterococci, which can die off in short periods of time and be highly transient (50,(54)(55)(56)(57). These findings support that nutrient concentrations and microbial communities are relatively stable over time and reflect longer-term conditions at a beach better than densities of fecal indicators.…”
Section: Discussionmentioning
confidence: 52%
“…The concentrations of these bacteria, however, are known to be highly variable (6,7,59,60). Intensive field studies show that their concentrations fluctuate on diurnal timescales due to sunlight exposure; concentrations drop during sunlit hours and rise after the sun sets (8,21,50,60,61). While enterococcal photoinactivation is well documented, the mechanisms of inactivation are not well understood, limiting our ability to predict when the process will be important under the wide range of conditions that exist in natural and engineered systems.…”
mentioning
confidence: 99%
“…Hourly sampling in South Korea resulted in similar conclusions: under dry weather conditions, sunlight inactivation of enterococci was responsible for a reduction of 1 to 2 orders of magnitude (59). A recent study showed that exceedances of current regulatory standards for enterococci at marine beaches (i.e., 104 CFU/100 ml) are more frequent during the night and late-afternoon hours (from approximately 6 p.m. to 8 a.m.) than during the morning and early afternoon, suggesting that sampling at different times of the day can significantly influence beach management decisions (100). Interestingly, a recent study described a possible mechanism for the extended survival of some enterococcal species exposed to sunlight: carotenoid pigment quenching of reactive oxygen species in certain strains appears to confer a competitive advantage against sunlight-induced inactivation (over nonpigmented isolates) (217).…”
Section: Responses To Environmental Stressorsmentioning
confidence: 99%